Fault-Based Test of XML Schemas - Emer, Maria Claudia Figueiredo Pereira; Nazar, Igor Fabiano; Vergilio, Silvia Regina; Jino, Mario (COMPUTING AND INFORMATICS, 2012)
XML is largely used by most applications to exchange data among different software components. XML documents, in most cases, follow a grammar or schema that describes which elements and data types are expected by the application. These schemas are translated from specifications written in natural language, and consequently, in this process some mistakes are usually made. Because of this, faults can be introduced in the schemas, and incorrect XML documents can be validated, causing a failure in the application. Hence, to test schemas is a fundamental activity to ensure the integrity of the XML data. With the growing number of Web applications and increased use of XML, there is a demand for specific testing approaches and tools to test schemas. To fulfill this demand, this work introduces a fault-based approach for testing XML schemas. This approach is based on a classification of common faults found in schemas. A supporting tool was implemented and used in evaluation studies. The obtained results show the applicability of the fault-based testing in this context and its efficacy in revealing faults.